Twisted bilayer graphene photoluminescence emission peaks at van Hove singularities. (3rd April 2018) - Alencar, Thonimar V; von Dreifus, Driele; Gabriela Cota Moreira, Maria; Eliel, Gomes S N; Yeh, Chao-Hui; Chiu, Po-Wen; Pimenta, Marcos A; Malard, Leandro M; Maria de Paula, Ana
Abstract: We report on photoluminescence emission imaging by femtosecond laser excitation on twisted bilayer graphene samples. The emission images are obtained by tuning the excitation laser energies in the near infrared region. We demonstrate an increase of the photoluminescence emission at excitation energies that depends on the bilayer twist angle. The results show a peak for the light emission when the excitation is in resonance with transitions at the van Hove singularities in the electronic density of states. We measured the photoluminescence excitation peak position and width for samples with various twist angles showing resonances in the energy range of 1.2 to 1.7 eV.